Evaluasi pelaksanaan pemantauan early warning score di tatanan perawatan medikal bedah - Christina, Tri Yahya; Putri, Rosalia Dian Arsyta; Safaruddin, Safaruddin; Sriwiyati, Lilik; Andika, I Putu Juni; Yulianti, Tunjung Sri (Holistik Jurnal Kesehatan, 2026)
Background: Deterioration in the condition of hospitalized patients is common and can have a more serious prognosis. Therefore, accurate and continuous monitoring of vital signs is crucial. The Early Warning Score (EWS) was developed as an effort to detect deterioration in patient condition early. Comprehensive and continuous EWS parameters, supported by clear implementation standards, are expected to save patients from deteriorating conditions. However, in medical-surgical care practices in Indonesia, the implementation of EWS monitoring still faces various obstacles that have the potential to delay early detection of patient deterioration, thus impacting patient safety. Therefore, an evaluation is needed. Purpose: To evaluate the implementation of Early Warning Score (EWS) monitoring in medical-surgical care settings. Method: This is a mixed-methods study with an exploratory sequential design. The sample consisted of 130 medical records and eight nurses who met the inclusion criteria. The medical record data obtained were analyzed using univariate analysis, while interview results were analyzed using content analysis. Results: The completeness of the EWS form remained at 44%, the accuracy of monitoring frequency was 12%, and the accuracy of the total score calculation was 3.8%. Several parameters contributing to the low level of form completeness include: blood sugar, which yielded a relatively low score (65%), followed by monitoring date (75%), level of consciousness (84%), monitoring frequency (86%), escalation scale (88%), initials (88%), blood pressure (89%), total score (89%), and suboptimal temperature (90%). These results align with the interview results, which yielded four themes: monitoring compliance, documentation compliance, appropriateness of temperature parameters, and non-specific EWS forms. Conclusion: Implementation of EWS monitoring in medical-surgical care settings still faces challenges that impact the effectiveness of the early warning system for patient deterioration. The study findings indicate a potential need for updating and/or developing the EWS system to meet hospital needs.   Keywords: Documentation; Early Warning System; Medical Surgical Nursing; Monitoring.   Pendahuluan: Penurunan kondisi pasien di rawat inap sering terjadi, bahkan memiliki proknosis yang lebih serius. Oleh sebab itu, pemantauan tanda-tanda vital yang akurat dan berkesinambungan sangat diperlukan. Early Warning Score (EWS) dikembangkan sebagai upaya untuk mendeteksi perburukan kondisi pasien sejak dini. Parameter EWS yang lengkap dan berkesinambungan yang didukung dengan standar implementasi yang jelas, diharapkan mampu menyelamatkan pasian dari kondisi yang lebih buruk. Namun, dalam praktik perawatan medikel bedah di Indonesia, pelaksanaan pemantauan EWS masih menghadapi berbagai kendala yang berpotensi menunda deteksi dini perburukan kondisi pasien yang berdampak pada keselamatan pasien. Oleh karena itu, evaluasi diperlukan. Tujuan: Untuk mengevaluasi pelaksanaan pemantauan Early Warning Score (EWS) dalam tatanan perawatan medikal bedah. Metode: Penelitian mixed-method dengan explanatory sequential design. 130 rekam medis dan 8 perawat yang sesuai kriteria inklusi diambil sebagai sampel. Data rekam medis yang diperoleh diolah secara univariat, sedangkan hasil wawancara diolah berdasar metode content analysis. Hasil: Kelengkapan pengisian formulir EWS masih mencapai 44%, ketepatan frekuensi monitoring 12%, dan ketepatan perhitungan total skor 3.8%. Beberapa parameter yang menyebabkan rendahnya tingkat kelengkapan pengisian formulir antara lain: parameter gula yang memberikan angka cukup rendah (65%), diikuti oleh tanggal pengjakian (75%), tingkat kesadaran (84%), frekuensi monitor (86%), skala eskalasi (88%), inisial (88%), tekanan darah (89%), total skor (89%), serta parameter suhu yang belum optimal (90%). Hasil ini sejalan dengan hasil wawancara yang menghasilkan 4 tema, yaitu kepatuhan pemantauan, kepatuhan dokumentasi, kesesuaian parameter suhu, dan formulir EWS yang tidak spesifik. Simpulan: Implementasi pemantauan EWS di tatanan praktik perawatan medikal bedah masih menghadapi tantangan yang memengaruhi efektivitas sistem peringatan dini perburukan pasien. Hasil penelitian menunjukkan adanya potensi kebutuhan pembaharuan dan atau pengembangan sistem EWS sesaui kebutuhan rumah sakit.   Kata Kunci: Dokumentasi; Early Warning Score; Medikal Bedah; Pemantauan; Perawatan.